Preferential infection of CD4+ memory T cells by human immunodeficiency virus type 1: evidence for a role in the selective T-cell functional defects observed in infected individuals. - Schnittman, S M (1990)
CD4+ T cells of patients with AIDS exhibit a qualitative defect in their ability to respond to soluble antigen while their responses to mitogens remain normal. CD4+ T cells can be broadly divided phenotypically into "naive" [CD45RA+ (2H4+)] and "memory" [CD29+ (4B4+) or CD45RO+ (UCHL1+)] cell subpopulations, which represent distinct maturation stages. To determine the human immunodeficiency virus type 1 (HIV-1) infectability of memory and naive CD4+ T-cell subsets in vitro and to determine the in vivo preference of HIV-1 in these subpopulations, we obtained highly purified CD4+ T-cell subsets from normal and HIV-1-infected individuals and studied them by viral cultivation, quantitative polymerase chain reaction, and functional assays. Polymerase chain reaction studies demonstrated that the memory cell subset of CD4+ T cells is preferentially infected (4- to 10-fold more than naive T cells) by HIV-1 in vitro, and these memory cells are the principal reservoir for HIV-1 within CD4+ T cells obtained from infected individuals. Functional abnormalities attributable to CD4+ T cells in HIV-infected individuals (failure to respond in vitro to soluble antigen or to anti-CD3 monoclonal antibodies) were shown to reside primarily within these memory cells. Thus, the present study suggests that the selective functional defects present in the memory CD4+ T-cell subset of HIV-infected individuals may be a direct result of the preferential infection and consequently greater viral burden within these cells.